Факт і норма у сфері соціального - Кабальський, Р. О.; Кабальский, Р. А.; Kabalskyi, R. A. (My University, 2016)
Стаття присвячена дослідженню нормативності як особливого феномена соціальної реальності. Автором доводиться, що питання про основоположні закономірності протікання процесів у природі та суспільстві існувало завжди, особливо коли соціальна реальність, нормативні засади й закони її функціонування отримали статус окремої проблеми. У зв’язку з цим запропоновано доцільність продовження дослідження проблеми нормативності в її соціокультурному вимірі. Автором з’ясовується співвідношення фактичного та нормативного як особливих феноменів суспільного простору. Доводиться взаємний вплив нормативних фактів із категорією норми й цінності. Запропоновано визначення нормативного факту та бачення його переходу в нормативну площину. Досліджено й запропоновано визначення правової нормативності.

Статья посвящена исследованию истории изучения нормативности как особого феномена социальной реальности. Автором доказывается, что вопрос об основоположных закономерностях протекания процессов в природе и обществе существовал всегда, особенно когда социальная реальность, нормативные основы и законы ее функционирования получили статус отдельной проблемы. В связи с этим предложена целесообразность продолжения исследования проблемы нормативности в ее социокультурном измерении. Автором доказывается связь и взаимозависимость нормативных фактов с категорией нормы и ценности. Предложены определение нормативного факта и видение его преобразования в норму. Исследовано и предложено определение правовой нормативности.

The article is devoted to the research of the history of the nature study of normativity as a special phenomenon of social reality. Although in the global philosophical thought the normativity as an independent philosophical category was hardly stood out separately, the author proves that the question of the fundamental laws of creation and existence of the universe, the laws of processes in nature and society has been always existed. With the development of the natural sciences and social sciences highlighting this issue acquired new meanings, shifting more in the social reality sphere. With the development of the world by means of natural sciences, social reality, normative principles and laws of its functioning, got the status of individual problems, resulting in the selection of a group of philosophers who were engaged in its study as opposed to natural reality. In connection with this it is suggested the extension advisability of the problem investigation of normativity in its sociocultural context. The article is devoted to research of the nature of normativity as a specific phenomena of social reality. The author proves the connection and interdependency of social normativity with the sphere of due which is implemented via a category of value. The definition of normativity as a social cultural phenomena is proposed.
Кабальський Р. О. Факт і норма у сфері соціального / Р. О. Кабальський // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2016. - Вип. 14. - С. 48-51.
Keywords: нормативний факт; норма; право; цінність; належне; загальнозначущість; нормативный факт; норма; право; ценность; должное; общезначимость; normativity; norm; value; due; constraint; general significance